2013
DOI: 10.2478/ijame-2013-0038
|View full text |Cite
|
Sign up to set email alerts
|

Variable Gravity Effects on Thermal Instability of Nanofluid in Anisotropic Porous Medium

Abstract: In this paper, we study the effects of variable gravity on thermal instability in a horizontal layer of a nanofluid in an anisotropic porous medium. Darcy model been used for the porous medium. Also, it incorporates the effect of Brownian motion along with thermophoresis. The normal mode technique is used to find the confinement between two free boundaries. The expression of the Rayleigh number has been derived, and the effects of variable gravity and anisotropic parameters on the Rayleigh number have been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Following the formalism of Nield and Kuznetsov [11], several studies were undertaken subsequently to investigate various additional effects on the problem by the same authors and others considering the volume fraction of nanoparticles is constant at the boundaries [12][13][14][15][16][17][18]. Recently, Nield and Kuznetsov [19] pointed out that this type of boundary condition on volume fraction of nanoparticles is physically not realistic as it is difficult to control the nanoparticle volume fraction on the boundaries.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Following the formalism of Nield and Kuznetsov [11], several studies were undertaken subsequently to investigate various additional effects on the problem by the same authors and others considering the volume fraction of nanoparticles is constant at the boundaries [12][13][14][15][16][17][18]. Recently, Nield and Kuznetsov [19] pointed out that this type of boundary condition on volume fraction of nanoparticles is physically not realistic as it is difficult to control the nanoparticle volume fraction on the boundaries.…”
Section: Introductionmentioning
confidence: 97%
“…Copious literature available on the non-Darcy-Benard convection in isotropic and anisotropic porous media is amply documented in the book by Nield and Bejan [20]. Chand et al [17] studied the effects of variable gravity on thermal instability in a horizontal layer of a nanofluid saturating an anisotropic Darcy porous medium. The intent of the present paper is to study the onset of penetrative convection in a horizontal layer of an anisotropic Brinkman porous medium saturated by a nanofluid via internal heating and heated uniformly from below.…”
Section: Introductionmentioning
confidence: 98%
“…They observed that the decreasing gravity parameter postponements the arrival of convective motion. The extension with anisotropic porous medium was also made by Chand et al Very recently, the weight of the variable gravity field on the magnetic nanofluid convection in a porous matrix was observed by Mahajan and Sharma . They proved that gravity coefficient postponements the start of convection.…”
Section: Introductionmentioning
confidence: 77%
“…Strughan [35] discuss the various type of variable gravity parameter on the stability convection and recently Chand [36][37] studied the variable gravity effects on the thermal instability in fluid layer. Effect of variable gravity in layer of nanofluid in a porous medium is studied by Chand et al [38] and found that gravity parameter play significant role on the stability of fluid.…”
Section: Introductionmentioning
confidence: 99%